PENGARUH SOLVABILITAS, SEGMEN OPERASI, DAN REPUTASI KAP TERHADAP AUDIT DELAY PADA PERUSAHAAN MANUFAKTUR DI INDONESIA - Kurniawati, Herni; Setiawan, Fanny Andriani; Kristanto, Septian Bayu (Jurnal Akuntansi, 2016)
Timeliness is one of the indicators used in the measure how quickly and accurately a company in publish financial reports in the context of decision making for investors. The information presented on time is considered able to provide a description of the condition that the company in a state of healthy both in the financial management internal control and routine operational activities. Audit delay is defined as a shift in the time that caused by delays in the settlement of the annual financial audit reports. This can occur because of a problem that appears not only from internal company but can also occur because of external factors. In this research we examined whether the solvency, operating segment of the company, and reputation Public Accountant (the big four and non-the big four) have an impact on the duration and scope of the work of the auditor. The object of this research is manufacturing companies listed in Indonesia Stock Exchange period 2011-2013. This research uses linear regression to test is whether or not the influence of solvency, operating segment and reputation Public Accountant to audit delay, aided by a software program eviews 6 and PASW Statistics 18. The results of this research are (1) the level of solvency of companies has positive effect on audit delay, (2) the number of business segments and the number of geographical segment has a negative effect on audit delay, (3) the reputation of Public Accountant has positive effect on audit delay.